Design, synthesis and biological evaluation of novel series of 2H-benzo[b][1, 4]oxazin-3(4H)-one and 2H-benzo[b][1, 4]oxazine scaffold derivatives as PI3Kα inhibitors. Issue 14 (7th August 2018) - Dong, Fu-Dan; Liu, Dan-Dan; Deng, Cheng-Long; Qin, Xiao-chun; Chen, Kai; Wang, Jian; Song, Hong-Rui; Ding, Huai-Wei
Graphical abstract: Highlights: Two series of novel 2 H -benzo[ b ][1, 4]oxazin derivatives were synthesized and characterized. Their antiproliferative activities against cancer cell lines were evaluated. 7f exhibited PI3Kα inhibitory activity with an IC50 value of 26.7 nM. 7f exhibited potent antiproliferative effects via PI3K/Akt signaling pathway inhibition. Abstract: The abnormal activation of PI3K signaling pathway leads to the occurrence of various cancers. The PI3Kα is frequently mutated and overexpressed in many human cancers. Therefore, the PI3Kα was considered as a promising target in therapeutic treatment of cancer. In this study, two series of compounds containing 2 H -benzo[ b ][1, 4]oxazin-3(4 H )-one and 2 H -benzo[ b ][1, 4]oxazine scaffold were synthesized and evaluated antiproliferative activities against three cancer cell lines, including HCT-116, MDA-MB-231 and SNU638. Compound 7f with the most potent antiproliferative activity was selected for further evaluation on normal cells and PI3K kinase. Studies indicated that compound 7f could decrease the phospho-Akt (T308) in a dose-dependent manner. Four key hydrogen bonding interactions were found in the docking of 7f with PI3K enzyme. All the results suggested that 7f was a potent PI3Kα inhibitor.